Behavioural responses of bean flower thrips (Megalurothrips sjostedti) to vegetative and floral volatiles from different cowpea cultivars - Diabate, S.; Deletre, E.; Murungi, L.K.; Fiaboe, K.K.M.; Subramanian, S.; Wesonga, J.; Martin, T. (Springer, 2019)
Bean flower thrips (Megalurothrips sjostedti) is a key pest of cowpea (Vigna unguicalata) in Africa. To better understand the interaction of M. sjostedti to cowpea cultivars to improve management efforts, we investigated the repellent properties of volatiles of four cowpea cultivars, namely Ex-Luanda, Machakos, Ken Kunde 1 and Katumani 80 at different phenological stages. Bioassays were conducted to study host preference and gas chromatography–mass spectrometry for chemical analysis of volatiles. Our results showed no significant preference of females M. sjostedti for any cowpea cultivars tested in preference assays. However, in olfactometer, the volatiles emitted during the vegetative stage of only Ex-Luanda, Machakos and Katumani 80 cultivars were repellent to females, while only Ken Kunde 1 was repellent to males. Volatiles from flowers of Ken Kunde 1 were attractive to females, whereas volatiles from the flowers of Katumani 80 were repellent, respectively. Ex-Luanda and Machakos elicited neutral response. Flowers of Machakos 66 and Ex-Luanda cultivars were repellent to males, while Katumani 80 and Ken Kunde 1 were neutral. The volatile analysis showed that (E)-β-ocimene and 1-octen-3-ol were unique to the volatile profile of Katumani 80 flowers. Previous study showed that (E)-2-hexenal and hexanal were only abundant in the vegetative stage of Katumani 80. (E)-2-hexenal was repellent to the females at a concentration of 0.01% but not at 1%. Hexanal, (E)-β-ocimene and 1-octen-3-ol elicited a neutral response from females at 0.01% and 1%. Our study indicates that (E)-2-hexenal could be useful in the development of semiochemical-based repellent tools for M. sjostedti management.